2014
DOI: 10.1002/qj.2492
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of naturally induced variability in the atmosphere using multiple reanalysis datasets

Abstract: A multiple linear regression analysis of nine different reanalysis datasets has been performed to test the robustness of variability associated with volcanic eruptions, the El Niño Southern Oscillation, the Quasi-Biennial Oscillation and with a specific focus on the 11-year solar cycle. The analysis covers both the stratosphere and troposphere and extends over the period 1979-2009. The characteristic signals of all four sources of variability are remarkably consistent between the datasets and confirm the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
146
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(180 citation statements)
references
References 93 publications
32
146
2
Order By: Relevance
“…However, there are some inhomogeneities in Modern Era Retrospective Analysis for Research and Applications upper stratospheric temperature (used for SAGE processing) due to drifting of the NOAA satellite platform carrying the stratospheric sounding unit (SSU) instruments [Wang et al, 2012], causing relatively small correlations even for SAGE v7.0 data. The effects of drifts in SSU temperatures on the SCS estimation are also discussed in Mitchell et al [2014].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some inhomogeneities in Modern Era Retrospective Analysis for Research and Applications upper stratospheric temperature (used for SAGE processing) due to drifting of the NOAA satellite platform carrying the stratospheric sounding unit (SSU) instruments [Wang et al, 2012], causing relatively small correlations even for SAGE v7.0 data. The effects of drifts in SSU temperatures on the SCS estimation are also discussed in Mitchell et al [2014].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are particularly relevant given the 10 uncertainties surrounding the observed atmospheric impacts of the 11-year solar cycle forcing (e.g. Mitchell et al, 2015a;2015b).…”
Section: Introductionmentioning
confidence: 94%
“…Gray et al, 2010). In the tropical upper stratosphere, a temperature change of ~0.7-1.1 K between solar maximum and minimum has been reported from rocketsonde and satellite data (Dunkerton et al, 1998;Ramaswamy et al, 2001;Keckhut et al, 2005;Randel et al, 2009;SPARC, 2010), with somewhat larger responses found in a number of reanalysis studies (Frame and Gray, 2010;Mitchell et al, 2015b). In addition to the temperature and ozone responses in the mid-/upper stratosphere, secondary tropical maxima have been identified in the 30 lower stratosphere; these are often explained to be of dynamical origin (see below).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there are still uncertainties in the observed atmospheric signals of solar variability (Mitchell et al, 2015a) and its transfer mechanism(s) to the surface. Proposed transfer mechanisms include changes in TSI and SSI, as well as in solar-driven energetic particles (e.g., .…”
Section: Introductionmentioning
confidence: 99%